Impact of distributed generations with energy storage devices on the electric grid - Srivastava, Anurag K.; Kumar, Aarthi A.; Schulz, Noel N. (My University, 2012)
The commonly used Distributed Generations (DG) technologies include wind generators, photovoltaics, and biomass generators with their sizes varying between several kW to a few MW. Energy storage devices are generally used to smooth variations in DG’s MW output due to inherent unpredictability and to minimize exchange of power from grid. Connecting the storage and DG’s to the grid have both technical and economic impacts. This paper aims at analyzing the technical and economic impacts of distributed generators along with energy storage devices on the distribution system. The technical analysis includes analyzing the transient stability of a system with DG’s and energy storage devices, such as a battery and ultracapacitor. The DG’s are represented by small synchronous and induction generators. Different types and locations of faults and different penetration levels of the DG’s are considered in the analysis. Energy storage devices are found to have a positive impact on transient stability. For economic analysis, the costs of the system with different DG technologies and energy storage devices are compared using the software tool “Hybrid Optimization Model for Electric Renewables (HOMER)”. Finally the analysis for cost versus benefits of DG’s and energy storage devices is compared briefly.
Keywords: Batteries; System economics; Energy storage devices; Power system transient stability; Distributed generation; Ultracapacitors